Regeneration a Southwark - Alistair Huggett (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
Examining the local politics of Borough, this work explains the modality with which the Department managed by Alistair Huggett, transformed the Bankside area. In the first part recalls the social-economic conditions of Southwark, borough in the centre of London, historically considered poor, with great sanitary problems and with a strong shortage of green spaces. In the second part examines the targets and the strategies of reclamation adopted by the Department, with a particular attention for the projects for Bankside and for the new Tate Modern, and for the subjects.